Ceramic Laminate Veneers for Reestablishment of Esthetics in Case of Lateral Incisor Agenesis - Geórgia Silva; Ana Cristina Normandes; Edson Barros Júnior; Joyce Gatti; Kalena Maranhão; Ana Cássia Reis; Fernanda Jassé; Lucas Moura; Thaís Barros (Hindawi Limited, 2018)
The increasing demand of patients looking for esthetics has resulted in the development of several techniques to restore anterior teeth. Conservative treatments should always be the first therapeutic option for the solution of aesthetic problems involving morphological changes and usually provide the result that the patient expects. In this context, ceramic laminate veneers, also known as "contact lenses," are capable to provide an extremely faithful reproduction of natural teeth with great color stability and periodontal biocompatibility. Minimal or no preparation veneers are heavily advertised as the answer to patients' cosmetic needs, when properly indicated by the dentist. This paper reports a clinical case where lateral incisor agenesis was aesthetically corrected using ceramic laminates.